The Role of Medium-Term Budgets in Enhancing Fiscal Sustainability and Service Delivery in South African Municipalities - Sifiso Mofokeng; Simon Matome Nkgapele (Research Synergy Foundation, 2025)
Fiscal sustainability and service delivery are crucial elements of fruitful governance, yet many South African municipalities struggle to manage these components. To address these problems, the government introduced medium-term budgets as a tool to make positive transformations in fiscal discipline and enhance service delivery. However, the success of these budgets in meeting these goals remains uncertain. To close this gap in knowledge, this article explored the role of medium-term budgets in promoting fiscal sustainability and improving service delivery in South African municipalities through a qualitative analysis of budget documents, policy reports and audit outcomes. The findings show that while some municipalities have benefited, many still face operational deficits, corruption, and a lack of skilled personnel, all of which hamper their effectiveness. This article recommends strengthening accountability mechanisms, investing in skills development, and improving financial monitoring systems. As a result, the article makes a vital contribution by providing significant insights for enhancing municipal budget execution and service delivery.